From orthodoxy to atheism: the apostasy of Bruno Bauer, 1835-1843 - Landry, Stan M. (The journal of religion & society, 2011)
This article is an intellectual and social history of the apostasy of the German theologian Bruno Bauer (1809-1882). It locates Bauer's intellectual and spiritual development from orthodox Protestantism to militant atheism in his exposure to historical criticism of the Bible, exclusion from German academic culture, and association with a group of Berlin atheists and dissidents. This is the first study dedicated exclusively to Bauer's apostasy. It underscores the personal experience of secularization and offers new insight into the complex intellectual and social processes behind individual apostasy and conversion.